2001
DOI: 10.1007/s002530100646
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a chitinase and an endo-β-1,3-glucanase from Trichoderma harzianum Rifai T24 involved in control of the phytopathogen Sclerotium rolfsii

Abstract: Of 24 Trichoderma isolates, T harzianum Rifai (T24) showed a potential for control of the phytopathogenic basidiomycete Sclerotium rolfsii. When T24 was grown on different carbon sources, growth inhibition of S. rolfsii by the T24 culture filtrate correlated with the activity of extracellular chitinase and beta-1,3-glucanase. The 43-kilodalton (kDa) chitinase and the 74-kDa beta-1,3-glucanase were purified from the T24 culture filtrate in two and three steps, respectively, using ammonium sulphate precipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
127
0
14

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(160 citation statements)
references
References 36 publications
19
127
0
14
Order By: Relevance
“…Our results on light microscopic study revealed that T. koningi MTCC 796 and T. harzianum NABII Th 1 showed effectively coiling on pathogen M. phaseolina at 14DAI, and may start the parasitism earlier during antagonism compared to other Trichoderma spp. Similar results have been reported for T. harzianum against Crinipellis perniciosa [34], Sclerotium rolfsii [35] and Rhizoctonia cerealis [36].…”
Section: % Growth Inhibitionsupporting
confidence: 79%
“…Our results on light microscopic study revealed that T. koningi MTCC 796 and T. harzianum NABII Th 1 showed effectively coiling on pathogen M. phaseolina at 14DAI, and may start the parasitism earlier during antagonism compared to other Trichoderma spp. Similar results have been reported for T. harzianum against Crinipellis perniciosa [34], Sclerotium rolfsii [35] and Rhizoctonia cerealis [36].…”
Section: % Growth Inhibitionsupporting
confidence: 79%
“…The optimum temperature reflects a balance between the effect on the activity and the maximum yield of the enzyme protein. This was positively correlated on the chitinase production by Trichoderma harzianum in submerged fermentation [14,15].…”
Section: Effect Of Ph and Temperaturementioning
confidence: 85%
“…It was supposed that the action of chitinase together with ␤-1,3-glucanase could act to hydrolyse the chitin and ␤-1,3-glucan from the cell walls of the sclerotia structure and release the laccase activity. The 43 kDa chitinase and 74 kDa ␤-1,3-glucanase were purified from the Trichoderma harzianum T24 culture filtrate as described previously [24]. When the harvested sclerotia were incubated separately with either of the two purified hydrolases, the laccase activity detectable in the supernatant was higher than that of the control (Table 2).…”
Section: Laccases From Sclerotiamentioning
confidence: 99%
“…This result suggests that when loaded together the enzymes acted in a synergistic manner leading to an increase in the laccase levels present in the supernatant. Synergistic interactions between chitinase and ␤-1,3-glucanase during biocontrol of S. rolfsii have previously been described [24].…”
Section: Laccases From Sclerotiamentioning
confidence: 99%
See 1 more Smart Citation